Perceived Social Support and Social Appearance Anxiety After Bariatric Surgery - Aliye Okgün Alcan; Meryem Yavuz van Giersbergen; Oğuz Doğan (Journal of Client-centered Nursing Care)
Background: Patients undergoing bariatric surgery may need much more psychological and social support from their family and friends to maintain weight loss, recover, and cope with social appearance anxiety. This study determines the relationship between perceived social support (PSS) and social appearance anxiety (SAA) after bariatric surgery. Methods: This descriptive, correlational study was conducted in Turkey between October and December 2022 through a voluntary response sampling technique. A total of 121 bariatric surgery patients generated the sample. The multidimensional scale of PSS (MSPSS) and the SAA scale were used for data collection. The data was analyzed by descriptive statistics, Mann-Whitney U, and Kruskal-Wallis tests. The SPSS software for Windows, version 21 was used for data analysis. A P<0.05 was considered statistically significant. Results: The mean total score of PSS of the patients was 60.28±19.62 and the mean scores of family, friends, and significant others regarding the source of the support were 24.88±7.19, 19.7±7.06, and 18.69±8.69, respectively. The average total score of SAA was 38.53±16.95. A statistically non-significant negative correlation existed between total scores of PSS and SAA (Spearman rho correlation coefficient [ρ]=-0.102 and ρ=0.27). The SAA total score differed according to gender, preoperative, and postoperative body mass index (P<0.05). Conclusion: The results showed that PSS does not affect SAA after bariatric surgery. Multicenter studies with more homogeneous samples in terms of time elapsed after bariatric surgery are recommended.